How Strategy Orientation Dimensions Affect Travel Agency Performance - Muhadjir Anwar; Ayundha Evanthi; Eko Purwanto (Nusantara Science and Technology Proceedings, 2023)
The current study intends to look at how organizational performance is influenced by the strategy orientation aspects of learning (LO), market orientation (MO), and entrepreneurial orientation (EO) in Indonesian travel agency companies. This study is a descriptive study in terms of the data collection methodology, an applied research study in terms of the intended audience, and a correlation study in terms of the data analysis. All 75 companies that operated in Indonesia's travel industry were included in the research statistical population. Data collection was done using a questionnaire. To test the hypotheses, the partial least square approach was employed. Analysis results indicated that MO mediates the relationship between performance and EO, EO also has a large direct impact on organizational performance, and EO mediates the implication of LO on performance.